Leaf morphology, rather than plant water status, underlies genetic variation of rice leaf rolling under drought - Cal, Andrew J.; Sanciangco, Millicent; Rebolledo, María Camila; Luquet, Delphine; Torres, Rolando O.; McNally, Kenneth L.; Henr, Amelia (Wiley, 2019)
Soil drying causes leaf rolling in rice, but the relationship between leaf rolling and drought tolerance has historically confounded selection of drought tolerant genotypes. In this study on tropical japonica and aus diversity panels (170‐220 genotypes), the degree of leaf rolling under drought was more affected by leaf morphology than by stomatal conductance, leaf water status, or maintenance of shoot biomass and grain yield. A range of canopy temperature and leaf rolling (measured as change in normalized difference vegetation index (ΔNDVI)) combinations were observed among aus genotypes, indicating that some genotypes continued transpiration while rolled. Association mapping indicated co‐location of genomic regions for leaf rolling score and ΔNDVI under drought with previously reported leaf rolling genes and gene networks related to leaf anatomy. The relatively subtle variation across these large diversity panels may explain the lack of agreement of this study with earlier reports that used small numbers of genotypes that were highly divergent in hydraulic traits driving leaf rolling differences. This study highlights the large range of physiological responses to drought among rice genotypes, and emphasizes that drought response processes should be understood in detail before incorporating them into a varietal selection program.